Copathologies in early‐ vs late‐onset Alzheimer's disease. (1st February 2022) - Spina, Salvatore; La Joie, Renaud; Petersen, Cathrine; Nolan, Amber L.; Cuevas, Deion; Cosme, Celica; Hepker, Mackenzie; Hwang, Ji‐Hye; Miller, Zachary A.; Huang, Eric J.; Karydas, Anna M.; Grant, Harli; et al.
Abstract: Background: Early‐onset AD (EOAD, onset of symptoms before age 65), is viewed as a relatively pure form of AD with a more homogeneous neuropathological substrate. Method: We sought to compare the frequency of copathologies in an autopsy series of 96 patients with EOAD (median age of onset (AOO) = 55 years, 44 females) and 48 with late‐onset AD (LOAD) (median AAO = 73 years, 14 females). The UCSF Neurodegenerative Disease Brain Bank database was reviewed to identify patients with a primary pathological diagnosis of AD. Prevalence and stage of Lewy body disease (LBD), limbic age‐related TDP‐43 encephalopathy (LATE), argyrophilic grain disease (AGD), hippocampal sclerosis (HS), cerebral amyloid angiopathy (CAA), and vascular brain injury (VBI) were compared between the two cohorts. Result: We found at least one non‐AD pathological diagnosis in 98% of patients with EOAD. LBD and CAA were common in both EOAD and LOAD (CAA: 86% versus 79%, Fisher exact p=0.33; LBD: 49% versus 42%, p=0.48, respectively), although amygdala‐predominant LBD was more commonly found in EOAD than LOAD (22% versus 6%, p=0.02). In contrast, LATE (35% versus 8%, p<0.001), HS (15% versus 3%, p=0.02), AGD (58% versus 41%, p=0.052), and VBI (65% versus 39%, p=0.004) were more common in LOAD than EOAD, respectively. The number of copathologies predicted worse cognitive performance at the time of death on MMSE (1.4 points/pathology (95%CI [‐2.5, ‐0.2]) and Clinical Dementia Rating – Sum of Boxes (1.15 point/pathology, 95%CI [0.45, 1.84]), across the EOAD and the LOAD cohorts. The effect of sex on the number of copathologies did not reach statistical significance (p = 0.17). Prevalence of at least one APOE e4 allele was similar across the two cohorts (52% and 54%) and was associated with a greater number of copathologies (+0.40, 95%CI [0.01, 0.79], p=0.047), independent of age of symptom onset, sex, and disease duration. Females showed higher density of neurofibrillary tangles compared to men, controlling for age of onset, APOE e4, and disease duration. Conclusion: Our findings suggest that non‐AD pathological diagnoses play an important role in the clinical phenotype of EOAD with potentially significant implications for clinical practice and clinical trials design.